The Effect of Bone Morphogenetic Protein 2 or Extracellular Signal-Regulated Kinase 1 Silencing on Phosphorus Utilization and Related Parameters in Primary Broiler Osteoblasts - Geng, Yanqiang; Li, Tingting; Hu, Yun; Zhang, Liyang; Cui, Xiaoyan; Zhu, Ling; Wu, Bingxin; Luo, Xugang (Frontiers in Veterinary Science, 2022)
Two experiments were conducted to study the effect of bone morphogenetic protein 2 (BMP2) or extracellular signal-regulated kinase 1 (ERK1) silencing on phosphorus (P) utilization and related parameters in primary broiler osteoblasts. Experiment 1 was carried out to select the most efficacious siRNAs against BMP2 or ERK1 for the subsequent experiment. In experiment 2, with or without the siRNA against BMP2 or ERK1, primary broiler osteoblasts were incubated in the medium supplemented with 0.0 or 2.0 mmol/L of P as NaH2PO4 for 12 days. The osteoblastic P utilization and related parameters were determined. The results showed that the si980 and si1003 were the most effective (P < 0.05) in inhibiting BMP2 and ERK1 expressions, respectively. The BMP2 silencing reduced (P < 0.004) the osteoblastic P retention rate, alkaline phosphatase (ALP) activity, BMP2 mRNA and protein expressions. Supplemental P increased (P = 0.0008) ALP activity. Significant interactions (P < 0.04) between the gene silencing and supplemental P level were observed in both mineralization formation and bone gal protein (BGP) content. The BMP2 silencing decreased (P < 0.05) mineralization formation at both 0.0 and 2.0 mmol/L of added P levels, but the decreased degree was greater at 2.0 mmol/L of added P level, while BMP2 silencing reduced (P < 0.05) BGP content at only 2.0 mmol/L of added P level. The ERK1 silencing decreased (P < 0.004) mineralization formation, ALP activity, BGP content, ERK1 mRNA, ERK1 and p-ERK1 protein expressions. Supplemental P increased (P < 0.03) mineralization formation, ALP activity, BGP content and p-ERK1 protein expression, but inhibited (P = 0.014) ERK1 protein expression. There was an interaction (P < 0.03) between the gene silencing and supplemental P level in the osteoblastic P retention rate. The ERK1 silencing decreased (P < 0.05) it regardless of 0.0 or 2.0 mmol/L of added P level, but the reduced degree was greater at 2.0 mmol/L of added P level. It was concluded that either BMP2 or ERK1 silencing suppressed P utilization, and thus either of them participated in regulating P utilization in primary broiler osteoblasts.